Adhesive cementation of zirconia posts to root dentin: Evaluation of the mechanical cycling effect - Galhano, Graziela Ávila Prãdo [UNESP]; de Melo, Renata Marques [UNESP]; Pavanelli, Carlos Augusto [UNESP]; Baldissara, Paolo; Scotti, Roberto; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2008)
This study evaluated the effect of mechanical cycling on the bond strength of zirconia posts to root dentin. Thirty single-rooted human teeth were transversally sectioned to a length of 16 mm. The canal preparation was performed with zirconia post system drills (CosmoPost, Ivoclar) to a depth of 12 mm. For post cementation, the canals were treated with total-etch, 3-steps All-Bond 2 (Bisco), and the posts were cemented with Duolink dual resin cement (Bisco). Three groups were formed (n = 10): G1 - control, no mechanical cycling; G2 - 20,000 mechanical cycles; G3 - 2,000,000 mechanical cycles. A 1.6-mm-thick punch induced loads of 50 N, at a 45° angle to the long axis of the specimens and at a frequency of 8 Hz directly on the posts. To evaluate the bond strengths, the specimens were sectioned perpendicular to the long axis of the teeth, generating 2-mm-thick slices, approximately (5 sections per teeth), which were subjected to the push-out test in a universal testing machine at a 1 mm/min crosshead speed. The push-out bond strength was affected by the mechanical cycling (1-way ANOVA, p = .0001). The results of the control group (7.7 ± 1.3 MPa) were statistically higher than those of G2 (3.9 ± 2.2 MPa) and G3 (3.3 ± 2.3 MPa). It was concluded that the mechanical cycling damaged the bond strength of zirconia posts to root dentin.
Keywords: Bond strength; Ceramics; Post and core technique; Stress, mechanical; resin cement; zirconium; zirconium oxide; analysis of variance; ceramics; chemistry; dental bonding; dental care; dentin; endodontics; human; instrumentation; materials testing; mechanical stress; methodology; standard; tensile strength; tooth crown; Analysis of Variance; Dental Bonding; Dental Stress Analysis; Dentin; Humans; Materials Testing; Post and Core Technique; Resin Cements; Root Canal Preparation; Stress, Mechanical; Tensile Strength; Zirconium